Leadership Position and Entrepreneurial Opportunity Recognition: Evidence from Lagos State, Nigeria - Okusanya, Adedoyin; Bamidele, Ayodeji; Obisanya, Adedoyin; Adenuga, Adesina (Universitas Pendidikan Ganesha, 2025)
Particularly in developing countries, Small and Medium Enterprises (SMEs) are crucial for economic growth and development. This study investigates the impact of leadership position on opportunity recognition in SMEs. The purpose is to examine how leadership positions influence entrepreneurs' ability to identify and capitalize on emerging opportunities in a dynamic business environment. Using a survey research approach, the study targeted 381 owners and managers of SMEs in the food and confectionary subsector in Lagos State, Nigeria. A structured questionnaire was used to gather data, and descriptive and inferential statistical methods, including regression analysis, were employed for data analysis. The results reveal that leadership position significantly influences opportunity recognition in SMEs (R² = 0.357, β = 0.601, t = 10.327, p = 0.05). Strategically minded leaders are better equipped to identify, assess, and seize business opportunities, driving growth and competitive advantage. The study concludes that leadership development is essential for SMEs to enhance opportunity recognition and recommends proactive leadership, organized training programs, and an environment that fosters innovation and strategic foresight. These findings contribute to the broader discussion on leadership and entrepreneurial behavior in developing countries.